Trauma and thyroid-stimulating hormone abnormalities in pediatric patients. (April 2020) - Aggarwal, Shefali; Fogel, Joshua; Kumar, Krishan; Shabbir, Nadeem
Background: There is limited literature on trauma and endocrine abnormalities in the pediatric trauma setting. Aim: We studied demographic, medical history, injury experience, and mortality factors to determine their association with abnormal thyroid-stimulating hormone in pediatric trauma patients. Methods: The 414 pediatric trauma patients were from those seen at an emergency department. The primary outcome variable was abnormal thyroid-stimulating hormone. Secondary outcome variables were abnormal high and abnormal low thyroid-stimulating hormone. Predictor variables were demographics (age, sex, race/ethnicity, body mass index), medical history (thyroid disease, diabetes mellitus, autoimmune disease, psychiatric disease), injury experience (injury cause, injury severity score ≥ 15, moderate/severe traumatic brain injury, length of stay), and mortality (mortality, survival probability). Multivariate logistic regression analyses were conducted. Results: There were 8.0% ( n = 33) with any abnormal thyroid-stimulating hormone value. In the analysis for abnormal thyroid-stimulating hormone, females (odds ratio:4.95, 95% confidence interval: 2.01, 12.21, p < 0.01) and traumatic brain injury (odds ratio: 8.11, 95% confidence interval: 2.51, 26.16, p < 0.001) were each significantly associated with increased odds. In the analysis for abnormal high thyroid-stimulating hormone (odds ratio: 3.75, 95% confidence interval: 1.37, 10.24, p < 0.05), traumatic brain injury (odds ratio: 11.59, 95% confidence interval: 3.45, 38.97, p < 0.001), and mortality (odds ratio: 35.59, 95% confidence interval: 1.40, 906.57, p < 0.05) were each significantly associated with increased odds. In the analysis for abnormal low thyroid-stimulating hormone, only females (odds ratio: 11.10, 95% confidence interval: 1.26, 97.60, p < 0.05) were significantly associated with increased odds. Conclusion: In conclusion, females and traumatic brain injury have increased odds for abnormal thyroid-stimulating hormone. Mortality has increased odds for abnormal high thyroid-stimulating hormone. We suggest that clinicians in the pediatric trauma setting carefully monitor females and traumatic brain injury patients with abnormal thyroid-stimulating hormone.